Characterization of Novel Hepatitis B Virus B/C Intergenotypic Recombinants in 3′-terminal Reverse Transcriptase Sequences among Chronic Hepatitis B Patients. (4th October 2017) - Liu, Baoming; Yang, Jing-Xian; Yan, Ling; Zhuang, Hui; Li, Tong
Abstract: Background: Chronic hepatitis B (CHB) remains a severe global public health concern. Hepatitis B virus (HBV) can be divided into 8 genotypes with different geographical distribution and virological features. We demonstrated genotypes B and C prevalent in southern and northern China, respectively, had divergent genotype-dependent amino acid polymorphisms and variations in reverse transcriptase (RT) gene, a target of anti-HBV therapy. Recently B/C intergenotypic recombination was reported in RT but its prevalence and clinical implications are elusive. This study aimed to characterize novel intergenotypic recombinants in HBV RT and to dissect their association with HBV-related clinical indexes. Methods: A total of 220 CHB cases were enrolled in China. Sera were tested for ALT, AST, or HBV serologic markers or DNA. HBV RT sequences were amplified, sequenced and genotyped. Recombination analysis was done with Simplot program. Results: 29.1% (64/220) of the cases had genotype B while 70.9% genotype C. Though no intergenotypic recombination was detected for genotype C, 37.5% (24/64) of genotype B HBV had recombination with genotype C at 3′ end of RT. No significant difference was found in ALT or AST, or HBeAg positive rate among the cases with the recombinants, or genotype B or C. Remarkably, HBV DNA of the untreated recombinant cases was significantly higher than that of pure genotype B group, though not significantly different from that of genotype C group. The untreated recombinants also had higher mutation rates at 7 residues throughout RT (rt53, 134, 213, 222, 271, 319 and 340) compared with parental genotypes, among which 3–4 substitutions were co-detected for one recombinant. Moreover, a majority of the recombinant HBV carriers were born on the South/North interface of China. Conclusion: Novel HBV B/C intergenotypic recombination at the 3' end of RT is associated with higher HBV DNA, interlinked RT point mutations and birthplace among Chinese patients. Our findings shed new light on the clinical, virological and epidemiological characteristics of novel intergenotypic recombinants. The emergence of new HBV recombinants may contribute to a dramatically enhanced heterogeneity in disease manifestations, treatment response and prognosis among CHB cases. Disclosures: All authors: No reported disclosures.